Efficacy Levels of Recombinant Tetravalent Dengue Vaccine (Cyd-Tdv) in Children Aged 2-16 Years: Meta-Analysis - Rayhana, Rayhana; Syahniar, Rike; Kharisma, Dayu Swasti; Aron, Belva Elrica; Kamsurya, Rizal (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Dengue fever is a type of disease with a high and fast transmission rate, especially in tropical and subtropical regions. One of the dengue fever vaccines developed by Sanofi Pasteur (CYD-TDV) and has undergone phase III clinical trials is the tetravalent dengue vaccine. This study aims to conduct a meta-analysis and review analysis of the effectiveness of the dengue vaccine on the level of efficacy at various age levels based on previously published research results. This research uses a quantitative approach through a meta-analysis study. The data in this study were obtained from multiple sources of scientific literature in the form of research articles published in national and international journals. Data was collected online through Google Scholar, PubMed, ProQuest, Cochrane Library, and Scopus—a literature search from various sources using the keyword dengue vaccine. Data analysis was performed with the distinct stages of the study sample, effect size heterogeneity testing, calculating summary effects, calculating p-values, and determining and plotting publication bias/trim-fill analysis. The research results showed that administration of the tetravalent vaccine (CYD-TDV) to children aged 2-16 years had a moderate relationship with a Random Effect value (r ̅_RE)=0.400. The efficacy level of the CYD-TDV dengue vaccine significantly impacts patients who are given the vaccine regularly at certain time intervals (I2=4.46%).